The Effect Of Yoga Exercise On Sleep Quality Among Menopausal Women : Literature Review - Fadlilah, Maya; Rashid, Norhashima Abd; Tan, Chun Hoe (International Journal of Health Sciences, 2023)
Introduction: Menopause causes changes in ovarian function which will automatically affect hormone production, which can cause various complaints. The increase in the number of elderly women will certainly cause its own problems, namely the emergence of complaints during menopause which can affect health. It causes discomfort and sometimes causes disruption in daily work, so it can affect the quality of life of menopausal women. Yoga is an effort to unite physical and physical strength and stimulate increased production of beta endorpine to reduce complaints due to menopause. The aim of this research is to determine the effect of yoga exercise on sleep quality and cognitive function in the elderly. This research is a literature review research. Material and Methods: This research examines topics related to the effect of yoga exercise on sleep quality in the elderly and menopause from previous studies. The literature reviewed and studied was 15 pieces of literature with 6 pieces of literature discussing the effect of yoga exercise on sleep quality in the elderly, especially during menopause. The literature consists of journals with a travel year from 2017 to 2023. Literature collection was done through Google scholar, Pubmed, and Science Direct by PRISMA. Results: The results of this study show that yoga exercises carried out regularly, both in the long and short term, can improve and improve the sleep quality of the elderly, especially menopausal women. Yoga exercise can also maintain the cognitive function of the elderly and prevent the elderly from dementia and Alzheimer's disease. Conclusion : The evidence is insufficient to suggest that yoga is an effective intervention for menopause. Further research is required to investigate whether there are specific benefits of yoga for treating menopausal symptoms.